The The Reaction of the Capital Market to Changes in Macroeconomic Variables: A Case Study of Bosnia and Herzegovina: The Reaction of the Capital Market to Changes in Macroeconomic Variables: A Case Study of Bosnia and Herzegovin - Alihodzic, Almir A.; Merdić , Alem; Dzafic, Jasmina (Industrija, 2026)
This study aims to identify the impact of macroeconomic and market variables on the stock market in Bosnia and Herzegovina. Two stock market indices on the capital market of Bosnia and Herzegovina are considered, namely the stock market index SASX-30 and BIRS. At the same time, macroeconomic and market variables are turnover (TRN), market capitalization (MC), export (EXP), import (IMP), gross domestic product (GDP), consumer price index (CPI), and foreign direct investment (FDI). The study adopts panel regression analysis for the period from 2013 to 2022. The results of the panel regression analysis showed that export and import values have the strongest influence in terms of significance on the movement of returns on the SASX-30 and BIRS stock market indices on the capital market of Bosnia and Herzegovina. On the other hand, the variables were achieved the lowest significance: turnover, market capitalization, foreign direct investments, and consumer price index.